ISLAMIC COUNSELING AND COUNSELING WITH COGNITIVE BEHAVIOR THERAPY TO PREVENT ANXIETY (MENTAL HEALTH PROBLEMS) A STUDENT AT ISLAMIC BOARDING SCHOOL OF SALMAN AL-FARISI KARANGANYAR SOLO - Din Muhammad Zakariya; Muh Iqbal Azhar Aziz (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2021)
This study aims to discuss how the implementation of Islamic Guidance and Counseling with cognitive behavior therapy (CBT) in preventing mental health problems of a student at the Salman Al-Farisi Islamic Boarding School Karanganyar Solo? (2) What are the results of students after undergoing the process of Islamic Guidance and Counseling with cognitive behavior therapy (CBT) in preventing mental health problems of a student at Islamic Boarding School Salman Al-Farisi Karanganyar Solo. This research uses qualitative research with descriptive analysis. In analyzing Islamic Guidance and Counseling with Cognitive Behavior Therapy in preventing mental health problems of a student at Islamic Boarding School Salman Al-Farisi Karanganyar Solo, the data presented in this chapter are data presentation in the form of interviews and observations. In this study, it was concluded that mental health problems (anxiety) experienced by a student greatly affected the client's mental and physical condition. From the counselor's observation before carrying out the counseling process, the problem experienced by a student was that he often experienced depression and anxiety that he had experienced. In handling this case, the counselor uses cognitive behavioral therapy, the counseling process uses interviews (face to face with clients) by directing how to think positively and behave well. By changing the client's attitude or behavior. The end result of this counseling process can be seen from a change in the client's attitude or the client's behavior that is not good enough to get better.